Center of mass velocity and the turn cycle in slalom - Haugen, P.; Reid, R.; Moger, T.; Tjørhom, H.; Gilgien, M.; Kipp, R.; Smith, G. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: There is a diversity of opinion among coaches as to where in a turn cycle skiers gain and lose speed. Knowing more about in which phases of the turn cycle a skier accelerates could lead to different technical and tactical approaches. The purpose of this study was to describe the time course of VCOM through a turn cycle.